Disinformation Operations Aimed at (Democratic) Elections in the Context of Public International Law: The Conduct of the Internet Research Agency During the 2016 US Presidential Election. (2019) - Rodriguez, Manuel
Abstract: Due to new technologies, the speed and volume of disinformation is unprecedented today. As seen in the 2016 US presidential election, especially with the conduct of the Internet Research Agency, this poses challenges and threats for the (democratic) political processes of internal State affairs, and in particular, (democratic) elections are under increasing risk. Disinformation has the potential to sway the outcome of an election and therefore discredits the idea of free and fair elections. Given the growing prevalence of disinformation operations aimed at (democratic) elections, the question arises as to how international law applies to such operations and how States under international law might counter such hostile operations launched by their adversaries. From a legal standpoint, it appears that such disinformation operations do not fully escape existing international law. However, due to open questions and the geopolitical context, many States refrain from clearly labelling them as internationally wrongful acts under international law. Stretching current international legal norms to cover the issue does not seem to be the optimal solution and a binding international treaty would also need to overcome various hurdles. The author suggests that disinformation operations aimed at (democratic) elections in the context of public international law will most likely be regulated (if) by a combination of custom and bottom-up law-making influencing and reinforcing each other.